2011
DOI: 10.1134/s0006297911090070
|View full text |Cite
|
Sign up to set email alerts
|

Selenoprotein dSelK in Drosophila elevates release of Ca2+ from endoplasmic reticulum by upregulating expression of inositol 1,4,5-tris-phosphate receptor

Abstract: dSelK (G-rich), a homolog of human and mouse SelK, is one of three selenoproteins in Drosophila melanogaster. It is the only trans-membrane selenoprotein in D. melanogaster integrated into both the endoplasmic reticulum (ER) membrane and the Golgi apparatus. The gene expression profile of Drosophila Schneider 2 (S2) cells after the dsRNA interference (dsRNAi) targeting of dSelK was examined with the GeneChip Drosophila Genome 2.0 Array (Affymetrix), a high-density oligonucleotide microarray encompassing nearly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 34 publications
1
10
0
Order By: Relevance
“…It was shown by ow cytometry that cytosolic free Ca 2+ level was elevated by the over-expression of mSelK and declined by the knockdown of mSelK in MIN6 b cells compared to the control group (Con) ( Fig. 2A and B), just like the results in Drosophila S2 cell line and human gastric cancer BGC 823 cell line by our group 35,36 and in T cells, neutrophils, and macrophages by Verma et al 37 And it was shown that aer the over-expression/knockdown of mSelK, the intracellular free Ca 2+ level was increased/ decreased to 149%/70% compared to the blank control group (taking blank control group as 100%), which suggested that the variation of free Ca 2+ level in MIN6 b cells by the overexpression/knockdown of mSelK was similar to that of the release of insulin.…”
Section: Effect Of Mselk On the Intracellular Free Ca 2+ Level In Minsupporting
confidence: 74%
See 3 more Smart Citations
“…It was shown by ow cytometry that cytosolic free Ca 2+ level was elevated by the over-expression of mSelK and declined by the knockdown of mSelK in MIN6 b cells compared to the control group (Con) ( Fig. 2A and B), just like the results in Drosophila S2 cell line and human gastric cancer BGC 823 cell line by our group 35,36 and in T cells, neutrophils, and macrophages by Verma et al 37 And it was shown that aer the over-expression/knockdown of mSelK, the intracellular free Ca 2+ level was increased/ decreased to 149%/70% compared to the blank control group (taking blank control group as 100%), which suggested that the variation of free Ca 2+ level in MIN6 b cells by the overexpression/knockdown of mSelK was similar to that of the release of insulin.…”
Section: Effect Of Mselk On the Intracellular Free Ca 2+ Level In Minsupporting
confidence: 74%
“…In our previous studies, it was shown that selenoprotein SelK in Drosophila S2 cells and human gastric cancer BGC 823 cells could increase the expression of inositol trisphosphate receptor (IP3R) on the ER, which increased the level of intracellular free calcium by promoting the release of Ca 2+ from ER to cytosol. 35,36 And this effect has been veried by others. 37,38 Further studies revealed that the stable expression of IP3R needs the palmitoylation of the protein, which requires the catalysis by an enzyme complex composed of DHHC6 (letters represent the amino acids aspartic acid, histidine, and cysteine in the catalytic domain) and selenoprotein SelK.…”
Section: Introductionmentioning
confidence: 81%
See 2 more Smart Citations
“…In a different study, SelK knockout mice exhibited deficiencies in calcium-related functions in the immune system [9]. A follow up study has shown that SelK undergoes proteolytic cleavage by m-calpain following Toll-like receptor activation [13] and is involved in regulation of inositol 1,4,5-tris-phosphate receptors [14]. …”
Section: Introductionmentioning
confidence: 99%